2016
DOI: 10.1177/0886260515625910
|View full text |Cite
|
Sign up to set email alerts
|

Perpetration and Victimization of Intimate Partner Violence Among Young Men and Women in Dar es Salaam, Tanzania

Abstract: We describe and compare the baseline rates of victimization and perpetration of three forms of intimate partner violence (IPV)—psychological, physical, and sexual—among sexually active men (n = 1,113) and women (n = 226) enrolled in an ongoing cluster-randomized HIV and gender-based violence prevention trial in Dar es Salaam, Tanzania. IPV was measured using a modified version of the World Health Organization Violence Against Women instrument. We assess the degree to which men and women report overlapping form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
55
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 33 publications
19
55
1
3
Order By: Relevance
“…The study also found high rates of co-occurrence of IPV victimization and perpetration, especially among IPV perpetrators, among both women and men. Similar results were found in a previous study in Tanzania (Mulawa et al, 2016). Although this study could not establish if IPV perpetration and victimization had happened within the same intimate relationship, a high probability of such overlap can be assumed given the 12 months reference period suggesting bidirectional IPV (Mulawa et al, 2016).…”
Section: Association Between Independent Variables and Ipv Victimizatsupporting
confidence: 81%
“…The study also found high rates of co-occurrence of IPV victimization and perpetration, especially among IPV perpetrators, among both women and men. Similar results were found in a previous study in Tanzania (Mulawa et al, 2016). Although this study could not establish if IPV perpetration and victimization had happened within the same intimate relationship, a high probability of such overlap can be assumed given the 12 months reference period suggesting bidirectional IPV (Mulawa et al, 2016).…”
Section: Association Between Independent Variables and Ipv Victimizatsupporting
confidence: 81%
“…Consistent with literature on adverse childhood experiences in developing country settings [31], we created a summative scale for cumulative exposures to violence, ranging from no exposures to violence, to exposure to four or more forms of violence during childhood. Demographic controls included age in years, if the respondent ever married, if he completed or attended secondary school or higher, and whether he ever begged in the street [19,31]. Potential confounders captured other adverse childhood experiences such as whether the respondent was orphaned (one or both parents died) before age 18 years, and the presence of social support from friends and family (e.g., if he felt very close to his biological mother and father, or if he reported talking with friends often about important things) [19].…”
Section: Methodsmentioning
confidence: 99%
“…In another multicountry study, which included data from two African countries, witnessing parental violence was a risk factor for men’s perpetration of physical IPV [18]. Additionally, research studies from Sub-Saharan Africa demonstrate associations between both experiencing violence in childhood [19,20] and witnessing parental IPV [21] with men’s perpetration of IPV. No population-based studies, to our knowledge, have explored the relationship between childhood exposures to violence and men’s perpetration of IPV against women in Malawi.…”
Section: Introductionmentioning
confidence: 99%
“…It could be that men who perpetrate violence to their partners while drunk blame it on alcohol when they sober up. Supportive literature to this finding was stated in studies [17,34,45] which indicated that harmful use of alcohol and/ or problem drinking was a precursor to experience of IPV.…”
Section: Discussionmentioning
confidence: 86%
“…These intermediate factors, most especially partner controlling behaviors precede and catalyse experience of IPV [15,32]. Also, harmful use of alcohol by a husband/partner was associated with increased likelihood of committing violence against the partner [13,17,33,34]. Incidents of children witnessing parental violence build up histories of violence and were highly associated with IPV [1,13,29].…”
Section: Introductionmentioning
confidence: 99%